LoRa-based DC Motor Control and Yagi Antenna - Alfiyanto Wahyu Wicaksono; Akhmad Nawawi; M. Erfin Prafitama S.; Yoko Herwanto; Widi Aribowo; Dimas Herjuno (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
With the advancement of wireless communication technology, appropriate solutions such as LoRa SX1278, a long-range intermediate module with a wider range of IoT applications have become available. Nevertheless, problems still exist, especially in Non-Line of Sight (N-LoS) circumstances that can favor transmission. On the other hand, the demand for more effective motors in the household sector is growing, where DC motors provide purchasing managers with advanced and low-cost direct control capabilities over AC induction motors. Suggested approaches include the use of omni-directional antennas to increase the transmission range of LoRa as well as the application of DC motors to improve operational efficiency. This work develops the necessary techniques to increase the communication range of LoRa and optimize the use of DC motors in a small industrial setting. The research procedure consisted of investigating the automatic control of a 12V DC motor using an Arduino Uno and a DHT22 temperature sensor, and the study of remote control via LoRa SX1278 with switching mode logic. The tests conducted confirmed that the percentage error of DC motor control was 0.78%, 0.42%, and 0.26% in each category, respectively. There is also a clear 600m and 6250m data transmission range on the LoRa in two different locations, featuring the same switching logic. In summary, the embellishment of LoRa SX1278 through omni-directional antenna anchoring and mode switching logic on the LoRa SX1278-based DC motor control system displays efficient operation and extended transmission range, thus offering antimicrobial potential in household industrial applications.